A new species of Leptogaster Meigen (Diptera, Asilidae) from Turkey with egg and spermatheca structure - Hasbenli̇ Abdullah; Candan Selami̇; Alpay Nesli̇han (Zootaxa, 2006)
Leptogaster suleymani n. sp. from South East of Turkey is described. Drawings of the male genitalia and the female spermatheca of this new species and the morphologically similar L. fumipennis Loew are given. Also, scanning electron micrographs of the spermatheca and eggs of this new species compared with L. fumipennis are given.